Pelatihan Revitalisasi Koperasi Desa Berbasis Transparansi Partisipatif di Jawa Tengah - Arif Nugroho; Siti Aisyah; Dedi Kurniawan; Rina Puspitasari; Ahmad Fauzi; Lilis Handayani; Rudi Prasetyo (Bakti Masyarakat Pengabdian dan Pemberdayaan Masyarakat, 2026)
Village cooperatives face serious challenges related to weak governance, low transparency in financial management, and minimal active participation of members in decision-making. This community service program aims to develop a participatory transparency-based revitalization training model for village cooperatives in rural areas of Central Java. The implementation method uses a participatory approach through governance workshops, Annual Member Meeting (RAT) simulations, financial reporting training, and six months of field mentoring involving 120 cooperative administrators, 45 supervisors, and 200 active members. Results showed a 79% increase in cooperative governance understanding, 71% improvement in financial report transparency, and 68% increase in member participation in RAT. Post-program evaluation indicated that 83% of partner cooperatives had implemented open reporting systems and 75% formed active internal supervisory teams. This program successfully created an accountable, transparent, and sustainably independent village cooperative ecosystem.